Backstepping Approach for Underactuated Systems - Nur Fadzillah, Harun; Zainah, Md. Zain (2014)
Control of underactuated systems usually required nonlinear technique because it cannot be stabilize with usual smooth, time-invariant and state feedback controller. Thus, backstepping approach is considered for stabilize underactuated systems, which the system is stabilized according to Lyapunov stability theory. This paper reviews the backstepping control method toward underactuated system.